Food availability in the heartland: effects of neighborhood race and income composition - Miller, Michael J. (Kansas State University, 2012)
Despite ideals of justice and equality, certain segments of the U.S. population are denied the rights and privileges available to the more affluent. This thesis examines the relationships between 1) neighborhood race and class composition and 2) food availability. We explore the extent to which physical and social isolation affects healthy food availability to groups marginalized by race and class. Specifically, we examine the relationship between residential racial and income composition and the availability of healthy foods. We use census tract data from the 2010 U.S. census and 5-year estimates from the 2006-2010 American Community Survey for Topeka, Kansas. For data on food stores we use InfoUSA, a professionally maintained database that provides detailed information on a variety of businesses. We verify this data with various “on the ground” techniques. We conclude with a discussion of the relevance of this work to the knowledge base regarding food environments in the United States.
Keywords: Food desert; Food insecurity; Urban segregation; Healthy food; Class segregation; Race segregation; Sociology (0626)